Micro-political games in the multinational corporation: The case of mandate change - Christoph Dörrenbächer; Mike Geppert (Management Revue, 2009)
Micro-political conflicts associated with corporate internationalization have been neglected by and large in the literature so far. Despite early consideration by the behavioral theory of internationalization, the specific strength of a micro-political approach, i.e. combining actors' idiosyncratic action with structural and institutional constraints, remained more or less unused in studies on corporate internationalization. Screening the relevant literature, discussing the strengths of micro-political approaches and proposing mandate changes in multinational corporations as an particularly interesting empirical field, the paper also outlines for some directions for further research into the micro-politics of multinational corporations.
Keywords: 650; multinational corporations; micro-political processes; game playing; mandate changes